2008
DOI: 10.1029/2008jb005710
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency acoustic‐gravity waves from coseismic vertical deformation associated with the 2004 Sumatra‐Andaman earthquake (Mw = 9.2)

Abstract: [1] Atmospheric pressure perturbations from the 2004 Sumatra-Andaman earthquake (M w = 9.2) were observed by sensitive microbarographs at several global stations. Among these observations, very low-frequency acoustic-gravity waves ($1.4-2.8 mHz) with a group velocity around 300-314 m/s and amplitudes ranging between $1 and 12 Pa can be clearly identified through data processing at four stations on the Japanese Islands and also at four International Monitoring System (IMS) stations around the Indian Ocean. Assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
36
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
(70 reference statements)
4
36
0
Order By: Relevance
“…We found the source of the first arriving acoustic-gravity wave about 300 km to the north of the US Geological Survey earthquake epicenter. This confirms the result of Mikumo et al (2008) that sea level changes at the earthquake source cause long period acoustic-gravity waves, which indicate that a tsunami was generated. Therefore, a denser local network of infrasound stations may be helpful for tsunami warnings, not only for very large earthquakes.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…We found the source of the first arriving acoustic-gravity wave about 300 km to the north of the US Geological Survey earthquake epicenter. This confirms the result of Mikumo et al (2008) that sea level changes at the earthquake source cause long period acoustic-gravity waves, which indicate that a tsunami was generated. Therefore, a denser local network of infrasound stations may be helpful for tsunami warnings, not only for very large earthquakes.…”
supporting
confidence: 78%
“…They also identified in the later parts of the records signals originating even from the northern part of the Bay of Bengal. Mikumo et al (2008) identified 500 s acoustic-gravity waves caused by swelling and depression of the sea surface and travelling with a speed of about 300 m s −1 . They used waveform modeling for determining the region of largest displacements of the seafloor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations